Explicit and Implicit Affect and Judgment in Schizotypy - Martin, Elizabeth A.; Hua, Jessica P. Y.; Straub, Kelsey T.; Kerns, John G. (Frontiers in Psychology, 2019)
Although emotion deficits in schizotypy have been reported, the exact nature of these deficits is now well understood. Specifically, for social anhedonia (SocAnh), there are questions about whether any decrease in positive affect only reflects an explicit bias not observed in other measures (e.g., implicit affect measure). At the same time, for individuals with elevated levels of perceptual aberrations or magical ideation (PerMag), there is some evidence of an increased influence of affect on judgment. It is also possible that the influence of implicit affect on judgment might be especially pronounced in PerMag; however, this has not been previously examined. The current study involved people with elevated levels of SocAnh (n = 95), elevated levels of PerMag (n = 62), and people with average or lower levels of both (n = 246). We found that SocAnh was associated with decreases in both explicit and implicit positive affect. We also found that PerMag was related to stronger relationships between implicit affect, both positive and negative, and a judgment task. These results suggest that decreased positive affect is a core feature of SocAnh and that a heightened influence of affect could be related to the development of peculiar beliefs/experiences associated with PerMag.